Simulating metallic contamination in permanent magnets used in magnetic sensors. Issue 5 (2nd September 2019) - Santos da Silva, Safire Torres; Jerance, Nikola; Rakotoarison, Harijaona Lalao
Abstract : Purpose: The purpose of this paper is to provide a model for simulating contamination by ferromagnetic particles in sensors that use permanent magnets. This topic is especially important for automotive applications, where magnetic sensors are extensively used and where metallic particles are present, particularly because of friction between mechanical parts. The aim of the model is to predict the particle accumulation and its effect on the sensor performance. Design/methodology/approach: Magnetostatic moment method is used to calculate particles' magnetization and magnetic field. Magnetic saturation is included and Newton–Raphson method is used to solve the non-linear system. Magnetic force on particles is calculated as a gradient of energy. Dynamic simulation provides the positions of agglomerated particles. Findings: A simulation of magnetic park lock sensor shows a significant impact of ferromagnetic particles on sensor's accuracy. Moreover, gains on computational time because of model optimizations are reported. Research limitations/implications: Only magnetic force and gravity are taken into account for particle dynamics. Mechanical forces such as friction and particle interactions might be considered in future works. Practical implications: This paper provides the possibility to evaluate and improve magnetic sensor design with respect to particles contamination. Originality/value: The paper presents a novel simulation tool developed to answer the growing need for reliable and fast prediction of magnetic position sensors' degradation in the presence of metallic particles.